Putative roles of the CNF2 and CDTIII toxins in experimental infections with necrotoxigenic Escherichia coli type 2 (NTEC2) strains in calves - Van Bost, Sigrid (Microbes Infect, 2003)
Newborn colostrum-restricted calves were orally inoculated with an Escherichia coli strain, identified originally as non-pathogenic, and into which the plasmid pVir was conjugally transferred. This resulted in diarrhea, intestinal lesions and extra-intestinal invasion, suggesting that factors affecting these pathogenic properties are located on pVir. In order to analyze the respective roles of the toxins CNF2 and CDTIII in the pathogenesis, colostrum-restricted calves were inoculated with isogenic mutants in the cnf2 and the cdt-III genes. The loss of cnf2 is associated with a reduction in the pathogenicity, since diarrhea does not occur in calves challenged, in spite of successful colonization of the intestine. Nevertheless, the mutant strain remains able to invade the bloodstream and to localize in the internal organs. Conversely, the calves inoculated with mutant in the cdt-III gene evolved in the same way as wild-type strain-inoculated calves with regard to clinical signs and macroscopic or microscopic lesions.